Invasive aspergillosis in children and adolescents with solid tumors: clinical cases and registry analysis - Yu. V. Dinikina; O. V. Shadrivova; M. B. Belogurova; Yu. E. Melekhina; S. M. Ignatyeva; T. S. Bogomolova; E. G. Boychenko; S. A. Kuleva; A. S. Kolbin; N. N. Klimko (Онкогематология, 2019)
We presented two cases of invasive aspergillosis (IA) in children with solid tumors, data of IA patients register, and a literature review. In the register of patients with IA (1997–2018), we found 57 patients with IA from 0 to 18 years. It was established that the number of patients with solid tumors was 15.7 %. Background diseases were: central nervous system tumors – 33.5 %, neuroblastoma – 33.5 %, osteosarcoma – 11.0 %, Wilms tumor – 11.0 %, hemangioblastoma – 11.0 %. Chemotherapy-induced neutropenia was reported in 100 % of IA cases in children and adolescents with solid tumors. The additional risk factors were treatment in intensive care unit – 22.2 %, high-dose chemotherapy with autologous hematopoietic stem cell transplantation – 22.2 %, concomitant bacterial infection – 33.0 %. Surgical intervention for the underlying disease was performed in 77.7 % of patients. The most common clinical site of IA was the lungs – 88.9 %. The predominant clinical sign was fever – 66.7 %, cough and respiratory failure were seen less frequently – 33.4 % and 33.4 %, respectively. The etiological agents of IA were Aspergillus fumigatus – 33.3 %, Aspergillus nidulans – 33.3 % and Aspergillus ustus – 33.3 %. 88.9 % of patients received antimycotic therapy, voriconazole predominantly – 66.7 %. Combination therapy was used in 33.3 % of patients. The overall 12-week survival in children and adolescents with IA in case of solid tumors was 77.8 %.